What does the Shinyei PPD42NS low-cost dust sensor really measure? (2021)
Abstract—Deteriorating air quality is of great concern around the world. Recently, citizen scientists, researchers, and many others have used low-cost devices such as the Shinyei PPD42NS dust sensor to measure particulate matter pollution in both developed and under-developed countries. However, few articles exist specifically on the features and performance of these sensors. Some have shown mixed results in terms of precision, accuracy, and repeatability, especially for portable applications. Frequently, users assemble the electronics and the sensors applying simple guidelines, using electric schematics, and coding extraneous algorithms to get questionable data. There is a need to better understand how it works exactly, its limitations and the effect of the program used to interpret the outputs of this sensor. This article provides a short electronic analysis of the Shinyei PPD42NS dust sensor and shows that the internal sensor electronic design (filters and detection stage) as well as the used data processing algorithm, limit its precision and accuracy by generating nonlinearities and biases. These issues avoid some applications like moving ones and imply that the algorithm used to process the sensor signals must be clearly presented in future articles.